Ethnic processes and culture among indigenous peoples of Chile (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Cultural issues in Chile are undergoing new dynamics and important transformations. During the past two decades, Chilean indigenous people‟s cultures have been circumscribed in the core of ethnical mobilizations and indigenous policies deployed by recent democratic governments. Cultural issues are both the basics and the strategic action object within the indigenous ethnogenesis developed during this period. Their formation as collective subjects rises up from access to their culture, which bestows upon them specificity. It also set itself up as an object of cultural policy and diverse ways of action. Indigenous cultural agents, specialized public agencies and civil society groups and institutions participate in this phenomenon. From this concurrence, a new process of social construction of indigenous cultural issues rises. Its structure takes the shape of a scope or a field of indigenous cultural issues in Chile.
Keywords: Indigenous culture; cultural change; ethnogenesis; cultural field